PENGARUH FINANCIAL DISTRESS, THIN CAPITALIZATION, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Atika Ulfani; Azhar, Iqlima; Nurismanidar (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to determine the extent of the influence of financial distress, thin capitalization, and company size on tax avoidance in automotive and component manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The researcher employed a quantitative research method. The sampling technique used was purposive sampling based on predetermined criteria. The analytical techniques utilized in this study included multiple linear regression analysis, t-tests, F-tests, and determination coefficient tests using SPSS version 20. The analysis results show that Financial Distress does not affect Tax Avoidance), Thin Capitalization affects Tax Avoidance, and Company Size does not affect Tax Avoidance. Simultaneously, the variables of Financial Distress, Thin Capitalization, and Company Size affect Tax Avoidance, with a coefficient of determination of 19.8%. This indicates that the independent variables can explain 19.8% of the variation in Tax Avoidance, while the remaining 80.2% is influenced by factors outside the scope of this study. The substantial Adjusted R2 value represents a limitation of this study; therefore, it is advisable for future research to incorporate additional variables such as transfer price, institutional ownership, and profitability.